Computerised cognitive training to improve cognition including delirium following coronary artery bypass grafting surgery: protocol for a blinded randomised controlled trial. Issue 2 (5th February 2020) - Greaves, Danielle; Psaltis, Peter J; Lampit, Amit; Davis, Daniel H J; Smith, Ashleigh E; Bourke, Alice; Worthington, Michael G; Valenzuela, Michael J; Keage, Hannah A D
Abstract : Introduction: Coronary artery bypass grafting (CABG) surgery is known to improve vascular function and cardiac-related mortality rates; however, it is associated with high rates of postoperative cognitive decline and delirium. Previous attempts to prevent post-CABG cognitive decline using pharmacological and surgical approaches have been largely unsuccessful. Cognitive prehabilitation and rehabilitation are a viable yet untested option for CABG patients. We aim to investigate the effects of preoperative cognitive training on delirium incidence, and preoperative and postoperative cognitive training on cognitive decline at 4 months post-CABG. Methods and analysis: This study is a randomised, single-blinded, controlled trial investigating the use of computerised cognitive training (CCT) both pre-CABG and post-CABG (intervention group) compared with usual care (control group) in older adults undergoing CABG in Adelaide, South Australia. Those in the intervention group will complete 1–2 weeks of CCT preoperatively (45–60 min sessions, 3.5 sessions/week) and 12 weeks of CCT postoperatively (commencing 1 month following surgery, 45–60 min sessions, 3 sessions/week). All participants will undergo cognitive testing preoperatively, over their hospital stay including delirium, and postoperatively for up to 1 year. The primary delirium outcome variable will be delirium incidence (presence vs absence); the primary cognitive decline variable will be at 4 months (significant decline vs no significant decline/improvement from baseline). Logistic regression modelling will be used, with age and gender as covariates. Secondary outcomes include cognitive decline from baseline to discharge, and at 6 months and 1 year post-CABG. Ethics and dissemination: Ethics approval was obtained from the Central Adelaide Local Health Network Human Research Ethics Committee (South Australia, Australia) and the University of South Australia Human Ethics Committee, with original approval obtained on 13 December 2017. It is anticipated that approximately two to four publications and multiple conference presentations (national and international) will result from this research. Trial registration number: This clinical trial is registered with the Australian New Zealand Clinical Trials Registry and relates to the pre-results stage. Registration number: ACTRN12618000799257.